La obligatoriedad de la mediación en accidentes de transito donde existan únicamente daños materiales - Morocho Benitez, Diego Oswaldo (2016)
This thesis takes as its theme: “MANDATORY MEDIATION IN TRAFFIC ACCIDENT WHERE THERE ARE ONLY DAMAGE “. This issue is very important, because in the traffic courts are many causes impounded by the court congestion; therefore it sought an extrajudicial way that simplifies this process; that is why mediation is the solution. This extrajudicially is protected in the Constitution of the Republic of Ecuador in his article Art. 190.- is recognized arbitration, mediation and other alternative methods for conflict resolution . These procedures shall be subject to the law in matters in which by their nature can compromise. That is why I feel obliged to do my research on where express the idea of amending Article 380 of Chapter Eight of traffic violations of the Code of Criminal Integral (COIP), which states: Art. 380. The person who as a result of a traffic accident causing material damage whose repair cost is greater than two salaries and not exceeding six unified basic salaries of workers in general, shall be punished by a fine of two unified basic wage worker in general and reduction of six points on your driver's license, without prejudice to civil liability to third parties that is subject because of the infringement. My idea is to add the article in question the obligation in a traffic accident where there are only material damage Ventilate and mediation; since this medium is more effective and efficient when solving conflicts of this nature. Mediation is a mechanism that will allow avoid the torturous time of the judicial process that sometimes seem eternal; also society should contribute to the peaceful settlement of disputes different types and make mediation a culture in our country. When there is only material damage in traffic accidents, people become aware of their guilt and want to reach an agreement to compensate the damage quickly and peacefully; they can not do, because the agents retain their vehicles and follow their procedure; here is where my reform proposal in the relevant law. Here we see the need to implement mandatory mediation prior to court proceedings but way; civil traffic police can issue its report to the center of mediation and by record or video record of the agreement and therefore that vehicles are not held back. I agree that mediation should not be in intentional crimes or at least when because of an accident death of a person or persons involved in the same or serious injuries occur in worse times; but this means if it is feasible to implement in cases like my research that simplify the agreements between the parties and make more effective access to justice.